2010
DOI: 10.1007/s11661-010-0499-5
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Ti Consolidated via Spark Plasma Sintering

Abstract: Cryomilled nanocrystalline commercially pure (CP)-Ti powders were spark plasma sintered (SPS) using different process parameters (heating rate, temperature, pressure, and dwell time) to study densification, microstructure, and mechanical behavior. The results were rationalized on the basis of the relevant literature and experimental results, and they reveal a strong dependence on SPS parameters. An interesting finding was that the measured high ductility was accompanied by a moderate strength (yield strength [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 76 publications
(137 reference statements)
0
22
0
Order By: Relevance
“…Each particle is repeatedly severely plastically deformed during the process causing an increase of dislocation density and a grain refinement. Ultra-fine grained (UFG) materials exhibit superior properties [14] and can be achieved by high-energy mechanical milling followed by appropriate compaction method [12,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Each particle is repeatedly severely plastically deformed during the process causing an increase of dislocation density and a grain refinement. Ultra-fine grained (UFG) materials exhibit superior properties [14] and can be achieved by high-energy mechanical milling followed by appropriate compaction method [12,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…4 [21]. Moreover, studies have revealed that the incremental changes in SPS dwell time does not increase the densification of nanostructured grade 2 Ti [39] as seen in Fig. 4.…”
Section: Sps Timementioning
confidence: 87%
“…As a result, further sintering did not increase the densification. The low difference between 3 and 5 min may also be another reason for remaining the relative density stable at this region [39].…”
Section: Sps Timementioning
confidence: 97%
“…Current research focuses mainly on bulk UFG materials produced by methods of severe plastic deformation (SPD), such as equal channel angular pressing [2] or high pressure torsion [3]. Nevertheless, UFG material can be also achieved by high-energy mechanical milling followed by appropriate compaction method [4][5][6].…”
Section: Introductionmentioning
confidence: 99%